PERILAKU KONSUMEN KERIPIK PISANG LUMER MELTE VANANA DI KOTA BANDAR LAMPUNG - Bayu Saputra; Yaktiworo Indriani; Yuliana Saleh (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to determine attitudes, satisfaction, and loyalty to purchasing Melte Vanana melted banana chips at CV Vanana Jaya Sinergi. This research is placed in Bumi Manti Street number II, LK II, Kampung Baru Village, Labuhan Ratu District, Bandar Lampung City chosen purposively. The number of samples in this study is 50 people selected by the non-probability sampling method. Research data is analyzed descriptively and qualitatively by Fishbein Multi-attribute Model, Consumer Satisfaction Index (CSI), and loyalty pyramid.  Results of the research known that consumers who became respondents in this study were 44 people (88%) aged 17-25 years and the majority were male. The highest level of consumer education is senior high school, with as many as 42 people (84%).  Most consumers' income or stipend (44%) is less than IDR500.000 per month.  Study results indicated that the consumer attitude score for Melte Vanana melted banana chips at CV Vanana Jaya Sinergi was 188.46 in the good category.  Consumer satisfaction with Melte Vanana melted banana chips at CV Vanana Jaya Sinergi was in the very satisfied criteria, with which score is 85.41. Consumers’ loyalty to Melte Vanana's melted banana chips was categorized as liking the brand (90%) at the loyalty pyramid level. Keywords: Attitude, banana chips, customer behavior, loyalty, satisfaction.